The rise of the French organ symphony with special reference to the works of Alexandre Guilmant and Charles-Marie Widor - Johnson, Bruce Richard (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 1990)
This thesis on the Rise of the French Organ Symphony refers especially to the relevant works of Alexandre Guilmant and Charles-Marie Widor. It commences with a survey of the historical background, dealing with the development of French organ music from the 16th to 19th Century and the development of organ building in France from the 17th to 19th Century. It then proceeds to descriptions of the organs of St Clotilde, La TriniteÌ and St Sulpice Churches in Paris, which are followed by biographical profiles of Cesar Franck, Alexandre Guilmant and Charles-Marie Widor, respectively. The major part of the thesis is devoted to a detailed analysis of the organ sonatas of Guilmant and the organ symphonies of Widor, which are discussed from the point of their cyclic outline and aspects of form and of style. The final chapter summarises the major findings of the analytical research and evaluates by comparative method, the merits and achievements of the two composers. In addition, Appendices are attached, providing specifications of various French organs and pictorial material relevant to the thesis. A separate cassette tape features characteristic sounds of Cavailie-Coll organs.
Keywords: Guilmant, Alexandre, 1837-1911; Widor, Charles-Marie, 1844-1937; Organ music -- History and criticism